2016
DOI: 10.11606/issn.1678-4456.v53i2p199-206
|View full text |Cite
|
Sign up to set email alerts
|

Use of an ultrasound device to determine sex and to perform gonad biopsy in the European eel Anguilla Anguilla

Abstract: The European eel Anguilla anguilla is a highly important market species which is also increasingly in danger of extinction in Europe. One of the ways of protecting the species in the natural environment, while maintaining its market supply, is its aquaculture, e.g. due to much higher survival rate under controlled conditions than in the wild. However, this can be done only when an effective artificial reproduction biotechnique is developed. The aim of this study was to use an ultrasound device to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These findings were proved by previous studies considering the small surgery as an effective method to determine the sex gender in Acipenser nudiventris (Hallajian et al, ) and Epinephelus merra (AshrafulAlam & Nakamura, ). The effectiveness of sex determination with accuracy 95% and 100% was reported in sexually immature and mature European eel, respectively (Kucharczyk et al, ). Falahatkar et al () reported sex determination of 3‐year‐old fish as 89.7%, 6‐year‐old fish as 95.4%, and 100% accuracy for 14‐year‐old fish, which were successfully identified through the biopsy procedure in the beluga sturgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were proved by previous studies considering the small surgery as an effective method to determine the sex gender in Acipenser nudiventris (Hallajian et al, ) and Epinephelus merra (AshrafulAlam & Nakamura, ). The effectiveness of sex determination with accuracy 95% and 100% was reported in sexually immature and mature European eel, respectively (Kucharczyk et al, ). Falahatkar et al () reported sex determination of 3‐year‐old fish as 89.7%, 6‐year‐old fish as 95.4%, and 100% accuracy for 14‐year‐old fish, which were successfully identified through the biopsy procedure in the beluga sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…USG was found to be effective in determining the sex of fish in the three‐year‐old beluga in which females and males were identified with 96.7% and 97.9% accuracy, respectively (Masoudifard et al, ). Furthermore, the USG method was successful in determining the sex of European eel ( Anguilla anguilla ) (Kucharczyk et al, ) and shovelnose sturgeon (Robert et al, ). In one study on shovelnose sturgeon, 86% accuracy was obtained with using the ultrasound method (Colombo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, since early 1980s, ultrasonography has been mainly used to determine the sex of numerous fish species, for conservation, research or aquaculture purposes. Among them, we can list coho salmon Oncorhynchus kisutch (Martin et al, 1983), Pacific herring Clupea pallasii (Bonar et al, 1989), Atlantic salmon Salmo salar (Mattson, 1991;Naeve et al, 2018), rainbow trout Oncorhynchus mykiss (Reimers et al, 1987), Atlantic halibut Hippoglossus hippoglossus (Martin-Robichaud & Rommens, 2001;Shields et al, 1993), striped bass Morone saxatilis (Blythe et al, 1994), Atlantic cod Gadus morhua (Karlsen & Holm, 1994;McEvoy et al, 2009), stellate sturgeon Acipenser stellatus (Moghim et al, 2002), shovelnose sturgeon Scaphirhynchus platorynchus (Colombo et al, 2004;Wildhaber et al, 2005), Murray cod Maccullochella peelii peelii (Newman et al, 2008), hapuku Polyprion oxygeneois (Kohn et al, 2013), European eel Anguilla Anguilla (Kucharczyk et al, 2016) or Chinese sturgeon Acipenser sinensis (Du et al, 2016).…”
Section: Introductionmentioning
confidence: 99%